Filter bag clogged in dust collector system / Amsyar Wajdi Ismail, Muhamad Helmi Affandi Adnan and Mohammad Zarriq Adzrin Mohd Poaad - Ismail, Amsyar Wajdi; Adnan, uhamad Helmi Affandi; Mohd Poaad, Mohammad Zarriq Adzrin (2018)
This case study report is based on the analysis and discussion on our study about dust collector system at BERNAS's factory. This company is GLC type business for supply of rice. We had made a visit to the company to analyse their dust collector system. An interview session with company's engineer has been done to learn about this system. We also were able to identify the issues and problems that the company faced and made discussions to find countermeasure. There were several problems that related to dust collector system.